Evaluation of Antioxidant Efficiency of Nanosized Quercetin: An In Vitro Study - Ghassan M. Sulaiman (Journal of Global Pharma Technology, 2016)
Quercetin is a bioactive compound that is widely used in botanical medicine due to its powerful antioxidant activity. This work aims at encapsulated of quercetin into PLGA nanoparticles by using the nano participation technique. Following by the valuation of their functionality as antioxidant activity. Quercetin and quercetin nanoparticles by using straight forward in vitro free radical scavenging systems including DPPH (1,1-diphenyl-2-picryl hydrazyl) free radical-scavenging assay and hydrogen peroxide radical scavenging. Quercetin nanoparticles showed strong scavenging effects against DPPH, hydrogen peroxide and this effect was more potent than pure quercetin. The scavenging activity of quercetin nanoparticles was concentrations dependent in the range of 4-12 µg mL-¹ showing maximum activity of 90% at 12 µg- mL-¹in similar way to Vit.C which was used as positive control. In conclusion, this work displayed that quercetin exhibited antioxidant activity and could be considered as a source of antioxidants from nature.Keywords: Quercetin nanoparticles, Antioxidants, DPPH, DNA damage.